TÜM ÜRETİM İÇERİSİNDEKİ MAL VE HİZMET HARCAMALARININ TÜRKİYE VE AB ÜLKELERİNDE MARKA PAZARLAMASI AÇISINDAN DEĞERLENDİRİLMESİ GENİŞLETİLMİŞ ÖZET (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2024)
In this research, it is aimed to evaluate the expenses of products and services in all production in terms of trademark marketing in Türkiye and EU countries. Trademark applications (TAR), Services value added (SVA), Goods and services expense (GSE), Industry value added (IVA), and Consumer price index (CPI) parameters from the World Bank Country Report from 2007 to 2020 were analyzed in the research. SVA (4.47±3.05) and GSE (10.30±1.09) means of Türkiye were higher than SVA (0.95±2.30) and GSE (8.47±0.76) means of the EU with statistically significant difference (p0.05). TAR was positively and highly correlated with CPI (r=0.951; p
Keywords: Mal; Hizmet; Marka; Türkiye; Avrupa Ülkeleri